2012
DOI: 10.1007/978-1-62703-074-8_12
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Embryogenesis for Efficient Micropropagation of Guava (Psidium guajava L.)

Abstract: Guava (Psidium guajava L.) is well known for edible fruit, environment friendly pharmaceutical and commercial products for both national and international market. The conventional propagation and in vitro organogenesis do not meet the demand for the good quality planting materials. Somatic embryogenesis for efficient micropropagation of guava (P. guajava L.) has been developed to fill up the gap. Somatic embryogenesis and plantlets regeneration are achieved from 10-week post-anthesis zygotic embryo explants by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The results of the present research showed that multiplication rate in double phase medium can be about two folds (13) compared to semisolid medium system. Considering the medium quantity needed for each system, gelling agent amount, labor related to subculture and washing glassware; it is estimated that double phase medium system can lower the total cost of plants by 20% compared to semisolid medium cultures system (Table 1) López y Suárez -In vitro multiplication of cane arrow Culture media for in vitro tissue culture can be formulated as semisolid, liquid or double phase (liquid on top of semisolid) (Akhtar, 2013;Mehta et al, 2014;Litwińczuk, 2013). Semisolid media favor explant stability and allow to expand the time for subculture because slow nutrient and water release to the tissues; in contrast, they are usually more expensive because of gelling agents costs and nutrient absorption by tissues is slower; in contrast, liquid media are less expensive for absence of gelling agents, nutrient and plant regulators absorption by explants is faster, especially in cell suspension systems; (El-Hawaz et al, 2015;Perera et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the present research showed that multiplication rate in double phase medium can be about two folds (13) compared to semisolid medium system. Considering the medium quantity needed for each system, gelling agent amount, labor related to subculture and washing glassware; it is estimated that double phase medium system can lower the total cost of plants by 20% compared to semisolid medium cultures system (Table 1) López y Suárez -In vitro multiplication of cane arrow Culture media for in vitro tissue culture can be formulated as semisolid, liquid or double phase (liquid on top of semisolid) (Akhtar, 2013;Mehta et al, 2014;Litwińczuk, 2013). Semisolid media favor explant stability and allow to expand the time for subculture because slow nutrient and water release to the tissues; in contrast, they are usually more expensive because of gelling agents costs and nutrient absorption by tissues is slower; in contrast, liquid media are less expensive for absence of gelling agents, nutrient and plant regulators absorption by explants is faster, especially in cell suspension systems; (El-Hawaz et al, 2015;Perera et al, 2015).…”
Section: Resultsmentioning
confidence: 99%